TOOLS OR SYSTEMS FOR IMPROVING ACCESSIBILITY TO FINANCIAL PRODUCTS AND SERVICES. - Njue, Michael Njeru; Mbogo, Marion (International Journal of Finance, 2017)
Purpose: The purpose of this study was to highlight the need for banks to develop financial products and services for small and medium enterprises. Methodology:The research design was descriptive survey study. The target population was 46 commercial banks .The sampling frame was the list of commercial banks given at the Central bank of Kenya Website. A sample of 17 banks was selected using random sampling. The second stage of sampling involved the selection of the respondents using a stratified sampling approach. The strata were the various departments that interact with SMEs in a bank. The respondents were the head of departments of the respective departments that form the strata. Both qualitative and quantitative data was collected using a questionnaire that consisted of both open ended and close ended questions. Data was analyzed using Statistical Package for Social Sciences (SPSS. Results: One of the study objectives was to establish the level of access to financial products and services offered by the banks to SMEs. Results from the bank manager's perspective indicated that the level of access to finance was high, but the bank clients indicated otherwise, that it was low. The other objective of the study was to determine the factors that hinder the SMEs from accessing the financial products offered by banks. Results indicated that several factors influence access of SMEs to finance. These factors include gender, level of education, size of the business, age of the entrepreneur, collateral, and level of income for the entrepreneurs. All the factors had a negative effect on the access of finances from the banks by SMEs and hence indicate SMEs low access to financial products. Another objective of the study was to establish the tools or systems required to improve accessibility to financial products offered. Results indicated that there are tools and systems put in place by banks to improve accessibility to financial products offered to small and medium enterprises. Unique contribution to theory, practice and policy:The study recommended that training be emphasized to SME entrepreneurs on financial matters, all gender to be treated equally, the banks to introduce financial education programs for SMEs to improve their access to credit, banks to further make use of a credit scoring system to assess the credit worthiness of small businesses and to introduce the use of new credit bureau regulations to increase SME finances.